2012
DOI: 10.1371/journal.pone.0046020
|View full text |Cite|
|
Sign up to set email alerts
|

Secreted Aspartic Protease Cleavage of Candida albicans Msb2 Activates Cek1 MAPK Signaling Affecting Biofilm Formation and Oropharyngeal Candidiasis

Abstract: Perception of external stimuli and generation of an appropriate response are crucial for host colonization by pathogens. In pathogenic fungi, mitogen activated protein kinase (MAPK) pathways regulate dimorphism, biofilm/mat formation, and virulence. Signaling mucins, characterized by a heavily glycosylated extracellular domain, a transmembrane domain, and a small cytoplasmic domain, are known to regulate various signaling pathways. In Candida albicans, the mucin Msb2 regulates the Cek1 MAPK pathway. We show he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 50 publications
(55 reference statements)
2
85
0
Order By: Relevance
“…albicans Sap8 mutants are hypervirulent in OPC. Our previous work suggested a possible role for Saps, and in particular Sap8, in the processing of signaling mucin Msb2 in C. albicans in vitro (32). To directly assess the role of SAP8 in vivo, we examined the virulence of a ⌬sap8 strain in murine oral candidiasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…albicans Sap8 mutants are hypervirulent in OPC. Our previous work suggested a possible role for Saps, and in particular Sap8, in the processing of signaling mucin Msb2 in C. albicans in vitro (32). To directly assess the role of SAP8 in vivo, we examined the virulence of a ⌬sap8 strain in murine oral candidiasis.…”
Section: Resultsmentioning
confidence: 99%
“…However, only germinated cells exhibited this aggregation, suggesting that cell surface molecules that permit Sap6-mediated cell-cell aggregation are exposed upon germination. It is unclear from our experiments whether Sap proteinases have an enzymatic role in cell wall remodeling to expose these adhesins, either directly or through MAPK signaling (32,35), since experiments to epithelial cell monolayers were infected with the CAI4 and SAP deletion strains for 90 min. After extensive washing, the adherent cells were harvested using 0.1% Triton X-100 and plated on YPD agar plates, and the plates were incubated at 30°C for 24 h to determine the numbers of CFU of adherent fungal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellularly, it acts to protect the pathogen against AMPs. It is currently debated if secreted aspartic proteases (SAPs) are responsible for the cleavage and release of the secreted Msb2 glycodomain, referred to as Msb2* (55,59). Msb2* inactivates a wide range of AMPs, including the human cathelicidin LL-37, Hst 5, hNP-1, and hBD1 by tight binding (Fig.…”
Section: Escape Strategies From Antimicrobial Peptidesmentioning
confidence: 99%
“…The precursor is cleaved and the exodomain released in substantial amounts into the environment during planktonic and surface growth (8,15,19). Previous studies suggested that the N-terminal, TM, and cytoplasmic domains of Msb2 convey different cellular functions (8).…”
Section: Albicans Strains Producing Msb2 Deletion Variantsmentioning
confidence: 99%